Integrated Analysis of Non-Coding RNA and mRNA Expression Profiles in Exosomes from Lung Tissue with Sepsis-Induced Acute Lung Injury - Deng W; Lu Y; Hu P; Zhang Q; Li S; Yang D; Zhao N; Qian K; Liu F (Dove Medical Press, 2023)
Wei Deng,1,2 Yanhua Lu,1,2 Ping Hu,1,2 Qingqing Zhang,1,2 Shuangyan Li,1,2 Dong Yang,1,2 Ning Zhao,1,2 Kejian Qian,1,2 Fen Liu1,2 1Department of Critical Medicine, The First Affiliated Hospital of Nanchang University, Nanchang, People's Republic of China; 2Medical Innovation Center, First Affiliated Hospital of Nanchang University, Nanchang, People's Republic of ChinaCorrespondence: Fen Liu, Email liufen9934@163.comBackground: Acute lung injury (ALI) is associated with a high mortality rate; however, the underlying molecular mechanisms are poorly understood. The purpose of this study was to investigate the expression profile and related networks of long noncoding RNAs (lncRNAs), microRNAs (miRNAs), and mRNAs in lung tissue exosomes obtained from sepsis-induced ALI.Methods: A mouse model of sepsis was established using the cecal ligation and puncture method. RNA sequencing was performed using lung tissue exosomes obtained from mice in the sham and CLP groups. Hematoxylin-eosin staining, Western blotting, immunofluorescence, quantitative real-time polymerase chain reaction, and nanoparticle tracking analysis were performed to identify relevant phenotypes, and bioinformatic algorithms were used to evaluate competitive endogenous RNA (ceRNA) networks.Results: Thirty lncRNA-miRNA-mRNA interactions were identified, including two upregulated lncRNAs, 30 upregulated miRNAs, and two downregulated miRNAs. Based on the expression levels of differentially expressed mRNAs(DEmRNAs), differentially expressed LncRNAs(DELncRNAs), and differentially expressed miRNAs(DEmiRNAs), 30 ceRNA networks were constructed.Conclusion: Our study revealed, for the first time, the expression profiles of lncRNA, miRNA, and mRNA in exosomes isolated from the lungs of mice with sepsis-induced ALI, and the exosome co-expression network and ceRNA network related to ALI in sepsis.Keywords: sepsis, acute lung injury, inflammation, lung tissue exosomes, ceRNA networks